The mental health impact of COVID-19: the need for community interventions and collaboration for recovery - Nadarajah Rajeshkannan; Daya Somasundaram; Balachandran Kumarendran; Thirunavukarasu Kumanan; Ivan Dinesh Aloysius; Nalayini Sugirthan; Sivanantham Sasikumar; Nalayini Jegathesan (Academia Medicine)
Background: Since 2019, the COVID-19 epidemic has spread across the world, affecting millions of individuals on physical, mental, and socioeconomic levels. Materials and methods: This qualitative study aims to map out the mental health consequences of the COVID-19 pandemic and suggest recovery strategies based on analyzing COVID-19 mental health and psychosocial impact-related comments on social/news media, participant’s observations, and participant action research. The results and suggested recovery strategies were triangulated with literature survey. Results: In COVID sufferers, neuropsychiatric symptoms lasting months were noted while some went on to have a relapse of psychological or neurological conditions. In the general population, common consequences included common mental health disorders, changing patterns of substance abuse particularly alcohol, and increased domestic violence. Family relationships and interactions generally improved but in a minority had strained dynamics. Vulnerable groups included the elderly, women, youth, children, disabled, frontline and health workers, minorities, and severely mentally ill. At the community level, there were signs of collective (mass) hysteria from panic buying to conspiracy theories, public shaming, fake news, and disinformation spreading on social media and mass protests. There were also positive effects such as better understanding of bio-knowledge, interventions and discoveries, online learning, gratitude toward health-care workers, increased community and family cohesion, reduction in road traffic accidents, and drop in other respiratory infections with their resultant morbidity and mortality. Conclusion: Given the widespread mental health consequences of the COVID-19 pandemic, a community-based approach is suggested while treating more severe mental disorders at the primary care or specialist level.